PEGylated Doxorubicin Prodrug-Forming Reduction-Sensitive Micelles With High Drug Loading and Improved Anticancer Therapy - Wang, Dongdong; Zhang, Xiaoyi; Xu, Bingbing (Frontiers in Bioengineering and Biotechnology, 2021)
Significant efforts on design and development of advanced drug delivery systems for targeted cancer chemotherapy continue to be a major challenge. Here we reported a kind of reduction-responsive PEGylated doxorubicin (DOX) prodrug via the simple esterification and amidation reactions, which self-assembled into the biodegradable micelles in solutions. Since there was an obvious difference in the reduction potentials between the oxidizing extracellular milieu and the reducing intracellular fluids, these PEG-disulfide-DOX micelles were localized intracellularly and degraded rapidly by the stimulus to release the drugs once reaching the targeted tumors, which obviously enhanced the therapeutic efficacy with low side effects. Moreover, these reduction-sensitive micelles could also physically encapsulate the free DOX drug into the polymeric cargo, exhibiting a two-phase programmed drug release behavior. Consequently, it showed a potential to develop intelligent and multifunctional chemotherapeutic payload transporter for the effective tumor therapy.